2021
DOI: 10.3389/fonc.2021.616133
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Autophagy-Related Signatures Identified Two Distinct Subtypes for Evaluating the Tumor Immune Microenvironment and Predicting Prognosis in Ovarian Cancer

Abstract: Ovarian cancer (OC) is one of the most lethal gynecologic malignant tumors. The interaction between autophagy and the tumor immune microenvironment has clinical importance. Hence, it is necessary to explore reliable biomarkers associated with autophagy-related genes (ARGs) for risk stratification in OC. Here, we obtained ARGs from the MSigDB database and downloaded the expression profile of OC from TCGA database. The k-means unsupervised clustering method was used for clustering, and two subclasses of OC (clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…However, due to inadequate sample size and the lack of available multi-omics data, only a few studies have applied genomic analysis to study OC from an immunological perspective. In our previous study, based on multi-omics data from the Cancer Genome Atlas (TCGA) cohort, we found that autophagy can affect the OC immune microenvironment ( 18 ). In the present study, to further explore the immune microenvironment of OC, we studied the impact of hypoxia on the immune microenvironment of OC.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to inadequate sample size and the lack of available multi-omics data, only a few studies have applied genomic analysis to study OC from an immunological perspective. In our previous study, based on multi-omics data from the Cancer Genome Atlas (TCGA) cohort, we found that autophagy can affect the OC immune microenvironment ( 18 ). In the present study, to further explore the immune microenvironment of OC, we studied the impact of hypoxia on the immune microenvironment of OC.…”
Section: Introductionmentioning
confidence: 99%
“…As clearly illustrated by Bru-seq trace diagrams (Figure ), QN523 increases the transcription of select autophagy-related genes WIPI1 (12.8-fold, Figure A), FAM129A (16.8-fold, Figure B), homocysteine-inducible ER protein with ubiquitin like domain 1 (HERPUD1) (9.8-fold, Figure C), GABARAPL1 (7.8-fold, Figure D), HMOX1 (13-fold, Figure E), and MAP1LC3B (6.8-fold, Figure F). WIPI1, GABARAPL1, and MAP1LC3B are well-established autophagy-related genes and relevant cancer markers at both gene and protein levels. HERPUD1 is a part of the ER-associated degradation machinery involved in ubiquitin-dependent degradation of misfolded proteins in the ER . FAM129A an ATF4 target genes plays a direct role in autophagy. , Heme oxygenase (HMOX1) acts as a cytoprotective gene against several forms of cell death including autophagy .…”
Section: Results and Discussionmentioning
confidence: 99%
“…There were some other studies concentrating on different features of biological process and the comprehensive analyses of functional related genes for OC [ 40 , 41 ], especially for lncRNAs. For example, one study identified and validated risk model based on five immune-related lncRNAs is an independent prognostic factor for OC patients.…”
Section: Discussionmentioning
confidence: 99%